In COVID-19 Times: A Qualitative Inquiry of the Experiences of Community-Based Organizations Serving North and Central Brooklyn Communities - Jennifer Pierre; Sheena Dorvil; Jocelyn Valdez; Shelby Boyle (International Journal of Environmental Research and Public Health, 2026)
Background: The COVID-19 pandemic exacerbated longstanding social and health inequities in predominantly Black and Latino communities in North and Central Brooklyn, in the form of disproportionately high hospitalization and mortality rates. Community organizations served as critical sources of information and resources during this period. Methods: The Bureau of Brooklyn Neighborhood Health within the NYC Health Department, conducted semi-structured virtual interviews with 19 representatives from 15 organizations that had partnered with the Bureau within the past five years. Interviews were conducted between November 2021 and February 2022. Transcripts were coded and analyzed using a hybrid deductive–inductive approach incorporating constant comparative techniques. Results: Partners described worsening food insecurity, inequitable vaccine and testing access, digital divide challenges, funding instability, staffing shortages, and escalating mental health needs. Organizations pivoted from routine operations to provide emergency food distribution, virtual programming, mental health support, advocacy, and disseminating information as trusted messengers in the community. Conclusions: Findings underscore the essential role of local community organizations in crisis response and recovery. Future preparedness efforts must center community expertise, strengthen cross-sector collaboration, streamline funding processes, and investments in social and digital infrastructures to advance health equity and community resilience.